2016
DOI: 10.1002/ar.23320
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative Effect of Grape Seed Proanthocyanidin Extract on Cadmium‐Induced Meiosis Inhibition During Oogenesis in Chicken Embryos

Abstract: Cadmium (Cd) is an environmental endocrine disruptor that has toxic effects on the female reproductive system. Here the ameliorative effect of grape seed proanthocyanidin extract (GSPE) on Cd-induced meiosis inhibition during oogenesis was explored. As compared with controls, chicken embryos exposed to Cd (3 mg/egg) displayed a changed oocyte morphology, decreased number of meiotic germ cells, and decreased expression of the meiotic marker protein gH2AX. Real time RT-PCR also revealed a significant down-regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…Recent studies have shown that GSPE could alleviate arsenic and cisplatin-induced oxidative stress in the testes of rodents [ 35 , 36 ]. Our previous study demonstrated that GSPE alleviated Cd-induced meiotic abnormalities of the ovarian tissues in chicken embryos [ 37 ]. In the present study, we investigated the effects of aging on ovary antioxidant status via comparing ovarian histology, antioxidants, and oxidants in the ovary and the expression levels of genes related to antioxidant capacity in ovaries of hens in different laying stages.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that GSPE could alleviate arsenic and cisplatin-induced oxidative stress in the testes of rodents [ 35 , 36 ]. Our previous study demonstrated that GSPE alleviated Cd-induced meiotic abnormalities of the ovarian tissues in chicken embryos [ 37 ]. In the present study, we investigated the effects of aging on ovary antioxidant status via comparing ovarian histology, antioxidants, and oxidants in the ovary and the expression levels of genes related to antioxidant capacity in ovaries of hens in different laying stages.…”
Section: Discussionmentioning
confidence: 99%
“…At morphological level, grape seed proanthocyanidins exerted positive effects in rat erythrocytes [34]. Simultaneous supplementation of grape seed proanthyocianidin extract (150 µg/egg) markedly improved the morphological alterations induced by cadmium as a result of upregulating meiosis-related proteins and gene expressions and restoring the antioxidant activity in embryo cells [35].…”
Section: Red Blood Cellsmentioning
confidence: 99%
“…At the opposite in the literature, a dietary selenium (antioxidant) supplementation increased hatchability and reduced embryonic mortality rate (48,49). Furthermore, using in ovo injection (at embryonic day 6.5), GSE has been shown to protect chicken embryos against Cadmium, an endocrine disruptor (29).…”
Section: Gse Supplementation Did Not Affect the Fertility Parametersmentioning
confidence: 99%
“…Recently, we showed that GSE treatments reduced OS and improved in vitro steroidogenesis without affecting cell proliferation and viability in human granulosa cells (27). In hens, grape seed proanthocyanidin extract could prevent the ovarian aging process by reducing oxidative stress (28) and could provide some protection against the reproductive toxicity induced by the Cadmium endocrine disruptor (29). However, no studies investigated the in vivo effects of the GSE on the egg performance (quantity and quality) and on the fertility parameters.…”
Section: Introductionmentioning
confidence: 99%